Customer Knowledge Management as a Success Driver for Business in Mobile Sector of Pakistan - Hafeez, Shakir; Hong, Li Lin; Saeed, Bilal Bin; Afsar, Bilal (International Review of Management and Marketing, 2017)
In this study, we reviewed the existing literature on customer knowledge management, paying special attention to the analytical and methodological studies, to define six success factors for assessing a company's customer knowledge management strategy. To assess these success factors, we opted to conduct a case study on Mobilink, Pakistan's leading telecommunications provider. Using our literature reviews, we devised a novel methodology that paired an external source-based assessment model, known as the Butterfly Model, and found that of the total 76 mechanisms outlined in the Butterfly Model, only 12 were not at all present at Mobilink, with a further 6 being unclear whether or not they were present also 47% of respondents agreed that grievances expressed by product consumers are a vital factor for thinking of and producing improved products, while another 40% mentioned that they thoroughly scrutinized the suggestions received by their customers before starting the major phase of the product development process. Around 37% of the respondents agreed that Mobilink encourage their customers to contribute in new and better products. The study concludes with some future directions by involving company stakeholders and academic researchers in customer knowledge management strategies Keywords: Customer Knowledge Management; Butterfly Model; Mobilink; Innovation; Pakistan Telecommunication JEL Classifications: D83, L96